Portable Solar-Battery Operated Grass Cutter - Jyoti M. Kharade; Sanika Bhagwan Bhalkar; Dhanashree Ramesh Deshmukh; Prajakta Adhik Khavale; Shambhuraje Jaywant Patil (International Journal of Engineering and Management Research, 2023)
One reason for the gradual increase in polution is increased fuel consumption. The solution is to use solar energy as an energy source to power batter powered lawn mowers. Our Portable Solar-Battery Operated Grass Cutter is actually a robotic body which contains a rechargeable battery, Direct Current (D.C) motors, Solar Panel, blade, an on-off switch and a button for area selection. Rechargeable battery is connected to Solar panel and supply is given to the ATMEGA 328 P microcontrollers which controls the further functions. Portable Solar-Battery Operated Grass Cutter Contains 5 DC motors. Where 4 DC motors are connected to four wheels of the robotic body and one DC motor is connected to the cutting blade to cut the grass. One ultrasonic sensor is used in our project which senses the grass and cut it. Button for Area Selection is provided to give the specifications of area to cut the grass and when the area is covered then the Portable Solar-Battery Operated Grass Cutter will stop.